2014
DOI: 10.1007/s12011-013-9880-8
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Functions and Trace Elements in Pediatric Patients with Exogenous Obesity

Abstract: Obesity is a multifactorial disease developing following impairment of the energy balance. The endocrine system is known to be affected by the condition. Serum thyroid hormones and trace element levels have been shown to be affected in obese children. Changes in serum thyroid hormones may result from alterations occurring in serum trace element levels. The aim of this study was to evaluate whether or not changes in serum thyroid hormone levels in children with exogenous obesity are associated with changes in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 24 publications
0
31
0
Order By: Relevance
“…Therefore, the trace elements in the body should be present in appropriate concentrations, and abnormal levels of trace metals can develop when the oxidation-antioxidation system fails [ 10 , 11 ]. It has been reported that thyroid gland is the organ with the highest levels of trace elements [ 12 ]. These elements have potential links with thyroid hormone metabolism, and any deficiency or excess can affect thyroid hormones homeostasis [ 3 , 13 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the trace elements in the body should be present in appropriate concentrations, and abnormal levels of trace metals can develop when the oxidation-antioxidation system fails [ 10 , 11 ]. It has been reported that thyroid gland is the organ with the highest levels of trace elements [ 12 ]. These elements have potential links with thyroid hormone metabolism, and any deficiency or excess can affect thyroid hormones homeostasis [ 3 , 13 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Typically, the contents of the chemical elements in relation to hypothyroidism were determined in serum [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ], blood [ 25 , 46 , 47 ], plasma [ 48 , 49 , 50 ] or urine [ 42 , 46 , 47 , 51 ]. The chemical, electrochemical, optical spectrometry, X-ray spectrometry, mass spectrometry, and nuclear methods are commonly used for the analyses.…”
Section: Resultsmentioning
confidence: 99%
“…The chemical, electrochemical, optical spectrometry, X-ray spectrometry, mass spectrometry, and nuclear methods are commonly used for the analyses. Atomic Absorption Spectrometry (AAS) proved to be the most popular analytical technique used especially for Se, Zn, Mn, Cr, Cu, Fe, and Pb determinations [ 27 , 28 , 29 , 31 , 35 , 36 , 37 , 38 , 40 , 45 , 46 , 48 , 50 ]. Inductively Coupled Plasma Mass Spectrometry (ICP MS) was applied for Mn, Cu, Zn, Se, Pb, Cd, Cr, and F [ 30 , 34 , 39 , 43 , 47 ], whereas Neutron Activation Analysis (NAA) for Fe, Cu, Zn, Se, respectively [ 25 , 52 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analytical methods can be employed in the study of the relation between the basic composition of body fluids and tissues, and the pathological conditions and general nutritional status in humans. The content of essential elements and toxic metals in human tissues and organs has been studied by many authors [7,8]. Heavy metals are known to cause a variety of health problems/diseases/injury, and mechanisms of their toxicity have been persistently investigated [9,10].…”
Section: Introductionmentioning
confidence: 99%